2007
DOI: 10.1063/1.2754643
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation reduction in GaN grown on stripe patterned r-plane sapphire substrates

Abstract: Extended defect reduction in GaN can be achieved via direct growth on stripe patterned (11¯02) r-plane sapphire substrates by metal organic chemical vapor deposition. The striped mesa is along [112¯0] with two etched sides in {0001} and {11¯01} faces. GaN grown on both etched facets in epitaxy exhibit different crystallographic relationships with sapphire substrate which are (11¯02)sapphire‖(112¯0)GaN and [112¯0]sapphire‖[1¯100]GaN, and (0001)sapphire‖(0001)GaN and [112¯0]sapphire‖[1¯100]GaN, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The growth of semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN was first demonstrated by Chen et al [46] who reported the fabrication of such grooved patterns on r-plane sapphire using a chemical wet-etching process. A SiO 2 mask, with 6 μm window regions and 1 μm mask regions, orientated along the [11][12][13][14][15][16][17][18][19][20] direction was deposited on r-plane sapphire using a standard photolithography technique.…”
Section: Selective Growth On Patterned Substratesmentioning
confidence: 99%
“…The growth of semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN was first demonstrated by Chen et al [46] who reported the fabrication of such grooved patterns on r-plane sapphire using a chemical wet-etching process. A SiO 2 mask, with 6 μm window regions and 1 μm mask regions, orientated along the [11][12][13][14][15][16][17][18][19][20] direction was deposited on r-plane sapphire using a standard photolithography technique.…”
Section: Selective Growth On Patterned Substratesmentioning
confidence: 99%
“…To improve the performance of GaN-based devices, there are several methods achieved in improving the epitaxial layer quality, including pendeo-epitaxy, nucleation layer growth, and epitaxial lateral overgrowth [1]. The epitaxy of GaN on patterned sapphire substrates (PSSs) has also been proved to effectively reduce the threading dislocation density [2]. It is well known that the epitaxial GaN layer grown on PSS always has a better quality than that grown on conventional sapphire substrate (CSS) characterized by the photoluminescence (PL), X-ray diffraction pattern, and lightemitting diode performance [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 This orientation is usually achieved by heteroepitaxially growing GaN on planar ͑1100͒ m-sapphire. 9 More recently, coalesced ͑1122͒ GaN films were achieved from r-sapphire patterned by plasma reactive ion etching. The resulting layers present however high densities of basal plane stacking faults ͑BSFs͒ and partial dislocations ͑PDs͒ terminating the BSFs, which are not commonly observed in c-plane GaN.…”
mentioning
confidence: 99%